Production of nanoarchitectonics corncob activated carbon as electrode material for enhanced supercapacitor performance. (1st November 2022) - Ortiz-Olivares, Rich David; Lobato-Peralta, Diego Ramón; Arias, D.M.; Okolie, Jude A.; Cuentas-Gallegos, Ana Karina; Sebastian, P.J.; Mayer, Adriana Reyes; Okoye, Patrick U.
Abstract: Corncob was utilized as a low-grade and abundant material for the production of activated carbon through impregnation with potassium carbonate (K2 CO3 ) at different ratios (1:1 to 1:3). The impregnated samples were activated at different temperatures (500 °C to 800 °C) and activated carbons were used to fabricate electrodes for energy storage. The results revealed that increasing activation temperature and K2 CO3 tailored the surface area (489–884 m 2 /g), morphological, and topography of the activated carbon to propagate higher energy storage via a predominantly electric double layer (EDL) mechanism. The capacitive performance of the materials obtained at different temperatures is in the order of 650 °C > 500 °C > 800 °C. In 3-electrode cells, a specific capacitance of 325 F/g was reached at a 5 mV/s scan rate. The energy retention and columbic efficiency after 10, 000 charge/discharge cycles were maintained at 88 % and 100 %, respectively. The corncob activated carbon material presented specific energy of 9.9 Wh/kg at 0.25 A/g, which is higher than many reported studies on activated carbon supercapacitors under similar conditions. Highlights: K2 CO3 activation at 650 °C resulted in mainly microporous activated carbon. A capacitance of 325 F/g at 5 mV/s was reached in a 3-electrode system. Corncob activated carbon delivered about 9.9 kW/g of energy. A 100 % columbic efficiency was maintained at 10, 000 cycles.